Family relations in Lisbon's business elite - Lima, A. P. (2002)
High status groups in Portuguese society constitute a social context in which familial relations are of great importance, both at the level of family members' daily agency and on the far broader scale of their social and professional relations. The author analyses in this article the way familial relations become important processes by which an elite social position may be maintained. The argument is based on fieldwork carried out by the author on seven leading business families in Lisbon who own large firms in operation for at least three generations. This research has showed that the processes by which these families manage to remain majority shareholders and in the top management position in the large companies they have owned for several generations is due, to a great extent, to the fact that these economic investments are considered the symbolic materialisation of a familial project. It is by means of carefully managing familial relations that those involved in these projects are able to ensure and reproduce their belonging to Portugal's financial and social upper set. This argument is illustrated throughout my research into the processes by which the leading families in Portugal's economic setting before the democratic revolution in 1974 have recovered their top financial and social positions in Portugal today.